2012
DOI: 10.1097/nna.0b013e3182619377
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nursing Surveillance in Keeping Patients Safe

Abstract: The most frequently reported threats to patient safety take place in hospitals, with the majority of errors and adverse events occurring during the course of routine care. Nursing surveillance has been proposed as an intervention to reduce adverse patient events. This article presents an overview and analysis of nursing surveillance with emphasis on the defining characteristics, antecedents, and consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 37 publications
1
44
0
1
Order By: Relevance
“…Scholars have identified the influence of organisational contexts on how healthcare providers define risks in relation to social imperatives and protecting their identity as a professional, which includes adherence to ethical standards and provision of quality care (Dixon‐Woods, Suokas, Pitchforth, & Tarrant, ). Moreover, the literature supports the effects of system constraints on enacting safety cultures (i.e., Aiken et al., ; Butler et al., ; Debourgh, ; Dickson & Flynn, ; Dresser, ; Jeffs et al., ; You et al., ).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Scholars have identified the influence of organisational contexts on how healthcare providers define risks in relation to social imperatives and protecting their identity as a professional, which includes adherence to ethical standards and provision of quality care (Dixon‐Woods, Suokas, Pitchforth, & Tarrant, ). Moreover, the literature supports the effects of system constraints on enacting safety cultures (i.e., Aiken et al., ; Butler et al., ; Debourgh, ; Dickson & Flynn, ; Dresser, ; Jeffs et al., ; You et al., ).…”
Section: Discussionmentioning
confidence: 89%
“…The findings of this study revealed that nurses were navigating the tensions of an organisational safety culture, constrained organisational resources and their own attitudes about important care, by constructing a definition of safety risks-preventing falls, removal of medical equipment and minimising disruption through restricting wandering. Butler et al, 2011;Debourgh, 2012;Dickson & Flynn, 2012;Dresser, 2012;Jeffs et al, 2008;You et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients’ length of stay (LOS) is frequently used as an outcome measure to evaluate whether nurses have enough time to monitor patients and quickly intervene when complications arise (Spetz, Harless, Herrera, & Mark, ). An improved surveillance for complications can lead to earlier interventions, which can result in earlier discharges and shorter LOSs (Dresser, ). Research on the association of the nursing workforce with LOS may provide better knowledge about the significance of nurse staffing for patient outcomes (Spetz et al., ).…”
mentioning
confidence: 99%